Controlling the Magnetic Properties of LaMnO3/SrTiO3 Heterostructures by Stoichiometry and Electronic Reconstruction: Atomic‐Scale Evidence. Issue 27 (17th May 2019) - Li, Mengsha; Tang, Chunhua; Paudel, Tula R.; Song, Dongsheng; Lü, Weiming; Han, Kun; Huang, Zhen; Zeng, Shengwei; Renshaw Wang, Xiao; Yang, Ping; Ariando,; Chen, Jingsheng; et al.
Abstract: Interface‐driven magnetic effects and phenomena associated with spin–orbit coupling and intrinsic symmetry breaking are of importance for fundamental physics and device applications. How interfaces affect the interplay between charge, spin, orbital, and lattice degrees of freedom is the key to boosting device performance. In LaMnO3 /SrTiO3 (LMO/STO) polar–nonpolar heterostructures, electronic reconstruction leads to an antiferromagnetic to ferromagnetic transition, making them viable for spin filter applications. The interfacial electronic structure plays a critical role in the understanding of the microscopic origins of the observed magnetic phase transition, from antiferromagnetic at 5 unit cells (ucs) of LMO or below to ferromagnetic at 6 ucs or above, yet such a study is missing. Here, an atomic scale understanding of LMO/STO ambipolar ferromagnetism is offered by quantifying the interface charge distribution and performing first‐principles density functional theory (DFT) calculations across this abrupt magnetic transition. It is found that the electronic reconstruction is confined within the first 3 ucs of LMO from the interface, and more importantly, it is robust against oxygen nonstoichiometry. When restoring stoichiometry, an enhanced ferromagnetic insulating state in LMO films with a thickness as thin as 2 nm (5 uc) is achieved, making LMO readily applicable as barriers in spin filters. Abstract : The ambipolar ferromagnetism in polar/nonpolar LaMnO3+ δ /SrTiO3 heterostructures is studied by macroscopic magnetic measurements, atomic‐scale scanning transmission electron microscopy, and electron energy loss spectroscopy. Electronic reconstruction generates electron‐doped ferromagnetism in LaMnO3 interfacial 3 unit cells, while oxygen nonstoichiometry induces hole‐doped ferromagnetism in the rest of the thin films. Vacuum‐annealed 2 nm LaMnO3 thin films are good ferromagnetic insulators and promising for spin‐filter applications.